Additional therapy for cholesterol lowering in ezetimibe-treated, statin-intolerant patients in clinical practice: results from an internal audit of a university lipid clinic. (2nd October 2016) - Cicero, Arrigo F.G.; Morbini, Martino; Bove, Marilisa; D'Addato, Sergio; Fogacci, Federica; Rosticci, Martina; Borghi, Claudio
Abstract: Objective: The aim of our study was to evaluate the tolerability and efficacy of alternative approaches to improve cholesterolemia control in patients with statin-related myalgia treated with ezetimibe. Research design and methods: We retrospectively evaluated 3534 Clinical Report Forms (CRFs) filled in the period June 2012–June 2015 for first visits to the lipid clinic of the University of Bologna. For this study, we selected 252 CRFs based on the following criteria: statin-related myalgia, previous failed treatment with at least two low-dosed statins, well tolerated treatment with ezetimibe. Then, the following lipid-lowering treatments were added in order to improve the ezetimibe low density lipoprotein cholesterol (LDL-C) lowering efficacy, based on clinical judgment: fenofibrate 145 mg, rosuvastatin 5 mg 1 tablet/week, rosuvastatin 5 mg 2 tablets/week, red yeast rice (standardized in monacolin K 3 mg) + berberine 500 mg, berberine 500 mg b.i.d., phytosterols 900 mg + psyllium fiber 3.5 g b.i.d. Patients continuing to claim a tolerable myalgia were then treated with coenzyme Q10 nanoemulsions 200 mg/day. Results: The treatment with standard lipid-lowering diet plus ezetimibe alone was associated with a mean LDL-C reduction of 17 ± 2%. The additive LDL-lowering effect with the various tested treatment was: −16 ± 2% with fenofibrate 145 mg/day, −13 ± 1% with rosuvastatin 5 mg 1 tablet/week, −17 ± 3% with rosuvastatin 5 mg 2 tablets/week, −19 ± 4% with red yeast rice + berberine, −17 ± 4% with berberine b.i.d. and −10 ± 3% with phytosterols + psyllium b.i.d.; 11% of the patients treated with fenofibrate required treatment modification because of myalgia recurrence, while the percentage was negligible for the other tested treatments. In patients with residual tolerable myalgia, treatment with coenzyme Q10 for 8 weeks was associated with a mean improvement of the graduated myalgia score from 4.8 ± 1.9 to 2.9 ± 1.3 ( p = 0.013). Conclusions: Some alternative treatments seems to be effective and well tolerated, thus improving the ezetimibe effect on cholesterolemia.